Exchange rate volatility and its effect on intra-East Africa Community regional trade - Mosbei, Thomas; Samoei, Silas Kiprono; Tison, Clement Cheruiyot; Kipchoge, Edwin Kipyego (Latin American Journal of Trade Policy, 2021)
East Africa Community exchange rate volatility spiraled up when the countries adopted the Structural Adjustment Policies in early 1980s. The question that remains unanswered is whether exchange rate volatility hinders or promotes trade. The objective of this study was to determine the effect of exchange rate volatility and its effect on Intra-East Africa community regional trade. Unit root tests results indicated that some of the variables were stationary at levels and on first difference, all variables were I(1). Differenced panel data was fitted into the General Autoregressive Conditional Heteroscedasticity model to measure volatility. Hausman test showed that the fixed effect model was appropriate exchange rate, money supply, population and foreign direct investment significantly determines intra-East Africa Community regional trade. It was concluded that exchange rate volatility is observable in the Intra-East Africa region and further, exchange rate, money supply, population, and foreign direct investment significantly influenced intra-EAC regional trade. It is recommended that EAC member states should formulate policies that ensures exchange rate stability in the region to reduce unpredictability of exchange rate. Policies should be enacted to guarantee adequate money supply and encourage foreign direct investments.